1980
DOI: 10.1002/jso.2930140106
|View full text |Cite
|
Sign up to set email alerts
|

Primary carcinoma of the gallbladder: A review of 328 cases

Abstract: A ten-year retrospective study of 328 histologically proven cases of primary carcinoma of the gallbladder between 1967 and 1976, with a two-year minimum follow-up was undertaken. The overall incidence was 2.9% of all cancer cases and 31.8% of all malignant tumours of the gastrointestinal tract. Male to female ratio was 1:2.64. The disease occurred on the average at a younger age in females (43 years) than in males (50 years). Pain and lump in the right upper abdomen were the commonest clinical features. Labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
2

Year Published

1982
1982
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 13 publications
2
10
0
2
Order By: Relevance
“…Piehler et al (1978) [12] reported male to female ratio of 1:3.2. Researchers in another studies reported that the incidence of GBC in females is two to three times higher than that in males [19][20][21][22][23]. Similar ratio was observed in the present study, the incidence of multiparous females in GBC group was significantly higher than that of control group.…”
Section: Discussionsupporting
confidence: 89%
“…Piehler et al (1978) [12] reported male to female ratio of 1:3.2. Researchers in another studies reported that the incidence of GBC in females is two to three times higher than that in males [19][20][21][22][23]. Similar ratio was observed in the present study, the incidence of multiparous females in GBC group was significantly higher than that of control group.…”
Section: Discussionsupporting
confidence: 89%
“…A large proportion of patients with these tumours, therefore, present at an advanced state. These tumours carry a very poor prognosis (5-year survival rate <12%) [4,5]. Surgery is the mainstay of treatment, but resection is possible in only 10-30% of patients [2].…”
Section: Discussionmentioning
confidence: 99%
“…It is particularly common in some of the developing countries [2,3] and has a very poor prognosis (5-year survival rate <12%) [4,5]. The anatomical location of the tumour and the late stage at which these tumours present contribute to the poor prognosis [6].…”
Section: Introductionmentioning
confidence: 99%
“…GBC is the most common malignancy of the gastrointestinal tract in women and the most common cause of malignant surgical obstructive jaundice in northern India . Several northern Indian centers had reported many experiences with GBC in the 1970s and 1980s . The All India Institute of Medical Sciences (AIIMS), New Delhi group has highlighted the dismal prognosis in patients with GBC ,.…”
Section: Gallbladder Cancer — An “Indian Disease”mentioning
confidence: 99%